The Effects of Different Row Spaces and Seeding Rates on the Hay and Crude Protein Yields of Sainfoin Onobrychis sativa - Necmettin Çelik; Mevlüt Türk (Journal of Agricultural Sciences)
The study was carried out to investigate the effects of different row spaces 15, 30, 45, 60 and 75 cm and seeding rates 40, 80, 120, 160 and 200 kg ha-1 on the hay and crude protein yields of sainfoin at the Agricultural Research and Experiment Center of Agriculture Faculty, Uludag University in 1999-2002. The field experiments were established in a split plot design with four replications. Plant height, stem number per m2, green matter yield, hay yield and crude protein yields were determined. The results suggested that sainfoin should be planted with 15-30 cm row spaces and at 160-200 kg ha seeding rate for hay production in Southern Marmara Region or in regions with similar ecological conditions